The State and International Development Management: Commentary from International Development Management Practitioners - Bertucci, Guido; Cooley, Larry; Fn'Piere, Patricia A.; Hughes, Paul D.; Manning, Nick (2012)
Poverty, instability, terrorism, and the emergence of new global actors characterize some of the central challenges facing twenty-first-century development and administration. Derick W. Brinkerhoff, a distinguished scholar in this field, delivered this Ferrel Heady Roundtable Lecture in 2007. He explores broadly the evolution of contemporary thinking concerning international development management. From his analysis, he draws thought-provoking clues regarding what works and what research questions remain to be answered. His central thesis: Lessons from past experience need to better inform current policy and practice. Five seasoned development administrators respond critically to Brinkerhoff's arguments, offering PAR readers an informative, insightful, and germane intellectual exchange.